Accuracy of Intravenous Infusion Flow Regulators in the Prehospital Environment. (3rd September 2018) - Loner, Carly; Acquisto, Nicole M.; Lenhardt, Heather; Sensenbach, Benjamin; Purick, Julie; Jones, Courtney M. C.; Cushman, Jeremy T.
Abstract: Objective : To assess the accuracy of multiple Intravenous Infusion Flow Regulators (IIFRs) at infusion rates and hanging heights common to the prehospital setting.Methods : Five different manufacturer's IIFRs were tested over a range of infusion rates while hanging at heights equivalent to the gurney pole, ambulance ceiling hook, and manufacturer's recommended height (if available). Each IIFR was run over a 15-minute period at each infusion rate and height three times. Drip effluent was collected and measured for comparison of volumes. Intra- and inter-device accuracy at different infusion rates and heights was calculated.Results : All devices deviated from the expected infusion volume regardless of infusion rate or height. There was inter-device variability across all IIFRs with some having reproducible though inaccurate volumes. Volumes were consistently below expected at lower heights and above expected at increased heights. Manufacturer recommended height guidelines provided slight improvements in accuracy.Conclusions : Significant deviations from expected IIFR volume were observed across all devices, flow rates, and heights in a static, laboratory environment. These findings would lend caution to the use of IIFRs as they could lead to inaccurate medication dosing (both over- or under-dosing) in the prehospital environment.